Prenatal diagnosis for de novo mutations: Experience from a tertiary center over a 10‐year period. Issue 4 (28th January 2019) - Eyal, Ori; Berkenstadt, Michal; Reznik‐Wolf, Haike; Poran, Hana; Ziv‐Baran, Tomer; Greenbaum, Lior; Yonath, Hagit; Pras, Elon
Abstract: Background: This study summarizes the results of prenatal diagnosis due to a history of de novo mutation in a previous pregnancy, in a tertiary center in Israel, over a 10‐year period. Methods: We sorted all cases of de novo mutations from a pool of 2, 260 pregnancies for which prenatal molecular diagnosis was applied, between the years 2008 and 2017. We identified 122 molecular prenatal diagnosis performed for de novo mutations, in 90 women. Results: While the total number of yearly prenatal diagnoses stayed stable, a linear increase was detected in the number of cases for which the procedure was done due to a previous de novo mutation: from 3 cases in 2008 to 24 cases in 2017. The most common diseases were Rett syndrome (19), neurofibromatosis Type‐1 (12) and Tuberous sclerosis (5). Recurrence occurred in 3 of the 90 women (3.3%) and hotspot mutations were identified in two genes accounting for 11 cases. We did not find a difference in paternal age at first occurrence of the de novo mutation between the study group and the control group. Conclusion: The large increase in the annual number of prenatal diagnoses performed due to a previous pregnancy with a de novo mutation reflects the growing understanding regarding the role of these mutations in the pathogenesis of genetic diseases. Abstract : A linear increase was detected in the number of cases for which the procedure was done due to a previous de novo mutation: from 3 cases in 2008 to 24 cases in 2017. The most common diseases were Rett syndrome (19), neurofibromatosis Type‐1 (12) and Tuberous sclerosis (5).